Ecological Low-Tech Architecture pada Pusat Kerajinan Terpadu: Studi Kasus di Pekanbaru - Ika, Nurul Tri Kartika (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, 2025)
One effort to preserve and develop crafts, which are part of the Malay cultural identity in Pekanbaru, is by designing a craft center that considers environmental and sustainability aspects. This design responds to the condition of urban buildings that tend to neglect local cultural values and comfort. The site is located in the rattan craft area of Pekanbaru City, which has the potential to attract tourists while providing comfort for visitors. The design process began with identifying problems, cultural potential, and the availability of local materials, then analyzed using the theory of Ecological Low-Tech Architecture and precedent studies to produce a contextual design that addresses environmental issues while strengthening cultural identity. Keywords: craft, Malay culture, sustainability, local materials